Students’ Awareness and Behavior towards E-Waste Management: A Study in Tobruk (Sebha University Conference Proceedings, 2024)
Libya is expanding in all sectors, which presents a significant difficulty when it comes to managing garbage, particularly e-waste. One of the most important strategies for reducing the production of e-waste is e-waste management. This necessitates taking the appropriate steps to change public awareness and disposal behaviour. This study was done among Tobruk Institute students. Surveys were given to 235 students who were registered for classes in April of the 2021 academic year. It recommends assessing students' attitudes and behaviours regarding e-waste management. In addition, the research aims to find out why devices need to be replaced as well as how students currently dispose of their electronic devices. This study used the analytical-descriptive approach by using (SPSS). The findings of this study show that only 55.9% of students have some awareness about e-waste. At the same time, the analysis of the students' behaviour indicates that, in general, they do not dispose of their electronic waste in an appropriate and environmentally friendly manner. This suggests that despite having some awareness about e-waste, the students' actual behaviour and practices when it comes to managing their own e-waste are lacking. The results have shown that the development of technology is the main reason behind replacing electronic products (54%). More than 80% of students replace their mobile phones within a period of less than two years. Keeping unused electronic products (PCs and laptops) at home was the most common method of discarding e-waste by students, and throwing mobile phones in the trash along with other waste was the second method.